Elektronik sistem nikah, cerai dan rujuk (e-SINAR) web - based islamic family and marriage managemenr system - Naimah, Talib (University Malaysia Sarawak, UNIMAS., 2005)
Electronic Sistem Nikah, Cerai dan Rujuk system (e-SINAR) is an application acceptance and processing system. This system is web-based system and each creation and processing task is made by online. The system provides processing links that links between user and administrator at Jabatan Agama Islam Sarawak (JAIS). The ability of e-SINAR is to accept the application process of pre-wedding, wedding ceremony and coonseling services, checks user application status and get much information about Islamic family development.